catena-Poly[[[tetraaquazinc(II)]-μ-4,4′-bipyridine-κ(2) N:N′] benzene-1,4-dicarboxylate] - Ruan, Ming-Bo (International Union of Crystallography, 2009)
In the title compound, {[Zn(C(10)H(8)N(2))(H(2)O)(4)](C(8)H(4)O(4))}(n), the Zn(II) atoms, lying on a twofold rotation axis, are bridged by 4,4′-bipyridine ligands, resulting in a linear chain along the b axis. In the chain, the Zn(II) atom adopts a slightly distorted octahedral coordination geometry involving four water molecules at the equatorial positions. The noncoordinated benzene-1,4-dicarboxylate anion, which is also located on a twofold rotation axis, bridges adjacent chains through O—H⋯O hydrogen bonds, forming a three-dimensional supramolecular network.